The modernization project of information and communication network of commercial banks on the basis of Dynamic Multipoint VPN technology - Пількевич, Ігор Анатолійович; Лобанчикова, Надія Миколаївна; Котков, Володимир Іванович; Кравченко, Ігор Володимирович (Eastern-European Journal of Enterprise Technologies, 2012)
The dynamic development of information security sphere constantly puts new demands on the creation of secure communication and information systems and networks in commercial banks. The information security of the commercial bank should be based on activities and technologies of information protection in the tools and networks of its transfer, processing and storage. The article analyzes the famous methods, approaches and technologies of creation of information and communication systems and networks in commercial banks. As a result of examination of existing methods and means of protection a range of defects, which should be eliminated with the corresponding project, was determined. To eliminate the determined defects it was suggested to apply the technology of multipoint virtual private network (VPN). The advantages of the suggested technology are: simplicity and visualization of setting, effective scaling, dynamic routing management, high operability, full-grown connected topology in terms of data transfer at a moderate volume of service traffic. Information and communication network has been designed in the software emulator GNS3 with the help of visual designer Cisco. The article represents a test example of circuit of protected information and communication network with Dynamic multipoint VPN technology